Evaluation of the effects of soda-lime-silica glass with rice husk ash as an additive on the hardness behavior - Alazemi, Mohammad F. F. S.; Ariffin, Mohd Khairol Anuar; Abdullah, Mohd Na'im; Supeni, Eris Elianddy; Abdul Aziz, Faieza (Growing Science, 2022)
Demand for eco-friendly materials increases each year due to their excellent properties, which has proved to contribute to developing a sustainable environment. One of the promising raw materials in producing Glass is rice husk, a waste product from paddy harvesting, containing about 90% of silica. Rice husks are usually burnt in an open area and contribute to severe air pollution problems. In this research, Soda-Lime-Silica Rice Husk Ash (SLRHA) glass which is a new combination of soda-lime silicate (SLS) glass and rice husk ash (RHA), was developed for building glass and window application. The hardness properties of the developed SLS-RHA glass system are presented in this paper. These glasses were investigated to determine the effect of RHA addition on the physical properties of SLS glass. The experimental works using RSM have successfully identified the significant factors and optimized the responses. Based on the Rockwell hardness test, the outcomes demonstrated that the glass sample contained 29.84% weight SLS and 0.06% weight RHA. The result indicated that crack propagation was increased with the increasing addition of RHA, which causes an increase in cracks and voids due to the creation of more debonding.